2013
DOI: 10.1186/1550-2783-10-8
|View full text |Cite
|
Sign up to set email alerts
|

Co-ingestion of carbohydrate and whey protein isolates enhance PGC-1α mRNA expression: a randomised, single blind, cross over study

Abstract: BackgroundWhey protein isolates (WPI) supplementation is known to improve resistance training adaptations. However, limited information is available on the effects of WPI plus carbohydrate (CHO) supplementation on endurance training adaptations.MethodSix endurance trained male cyclists and triathletes (age 29 ± 4 years, weight 74 ± 2 kg, VO2 max 63 ± 3 ml oxygen. kg-1. Min-1, height 183 ± 5 cm; mean ± SEM) were randomly assigned to one of two dietary interventions in a single blind cross over design; CHO or CH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 44 publications
6
47
1
1
Order By: Relevance
“…It will be necessary in future studies to determine insulin levels at multiple time points in the first 60 min after food ingestion. However this interpretation is in line with published data showing that protein/carbohydrate beverages increase insulin levels stronger then carbohydrate beverages [13,17].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…It will be necessary in future studies to determine insulin levels at multiple time points in the first 60 min after food ingestion. However this interpretation is in line with published data showing that protein/carbohydrate beverages increase insulin levels stronger then carbohydrate beverages [13,17].…”
Section: Discussionsupporting
confidence: 81%
“…Effects of ingestion of protein/carbohydrate combination's after endurance exercise on of skeletal muscle damage and recovery have been described in the literature and mechanistically linked to a stimulation of insulin secretion [17]. Therefore in this study we have monitored blood glucose levels and also insulin levels at different time points after exercise and protein carbohydrate ingestion.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this response was also associated with increased peroxisome proliferator-activated receptor-γ (PPAR-γ) activation and expression of PPARγ-coactivator-1α (PGC-1α), putative transcriptional regulators of mitochondrial proteins (Rowlands et al, 2011). Importantly, these findings support recent work demonstrating that 2 weeks of protein-carbohydrate supplementation with endurance training increased PGC-1α mRNA compared with a carbohydrate-only intervention (Hill et al, 2013). We have also shown that protein ingestion increases PGC-1α mRNA following a bout of concurrent resistance and endurance exercise, although this response occurred despite there being no change in mitochondrial protein synthesis rates .…”
Section: Reduced Energy Availabilitysupporting
confidence: 79%
“…Endurance exercise influences and stimulates PGC-1α expression (Hill, Stathis, Grinfeld, Hayes, & McAinch, 2013;Lira, Benton, Yan, & Bonen, 2010); even a single exercise bout exerts these effects (Hill et al, 2013). This concept is in accordance with our findings, where the PGC-1α expression increased in all exercised groups, except for Val-Leu group, compared with the control (rest) group.…”
Section: Discussionsupporting
confidence: 93%